Graded Division Rings - Balaba, Irina N.; Mikhalev, Alexander V. (Sarajevo Journal of Mathematics, 2019)
In this paper the survey of the results concerning graded division rings is given. Even though that the graded division rings are not division rings in the usual sense the graded modules over graded division rings have properties similar to those of the linear spaces. We consider the properties of the graded linear spaces and graded rings of linear transformations, describe the isomorphisms and anti-isomorphism of graded rings of linear transformations.